ANALISIS KESIAPAN GURU IPA DALAM IMPLEMENTASI KURIKULUM 2013 DI SMP NEGERI SEKECAMATAN STABAT - Layil Safitri (JURNAL TEMATIK, 2018)
This study aims to determine the readiness of science teachers in SMP preparing for learning by implementing the 2013 curriculum in SMP Negeri sekecamatan Stabat. The type of this research is quantitative descriptive analysis. The subjects in this study were 2 science teachers SMP Nigeria 1 Stabat, 4 science teachers SMP Nigeria 2 Stabat, and 5 teachers IPA SMP Nigeria 5 Stabat. Data on the readiness of science teachers in the implementation of the 2013 curriculum were collected through questionnaires and observation sheets. The results showed that: Science Teachers of SMP Nigeria in Stabat Sub-district stated ready in preparing the learning curriculum 2013, this can be seen from the average percentage of 79% with the ready category; Science Teachers of SMP Nigeria in Stabat Sub-district have categories ready to prepare the learning tools of curriculum 2013, this can be seen from the data as follows: Average percentage of science preparedness science teachers SMP Nigeria 1 Stabat by 79% with ready category. The average percentage of teachers prepared science IPA SMP Nigeria 2 Stabat 70% with categories ready. The average percentage of preparedness of science teachers of state SMP 5 Stabat is 78% in ready category.